The synthesis of large crystals of zeolite Y re-visited - Berger, Christine; Gläser, Roger; Rakoczy, Rainer A.; Weitkamp, Jens (Microporous and mesoporous materials, 2005)
The major synthesis routes described in the literature so far for zeolite Y (FAU) with an elevated n Si/ n Al-ratio and larger crystallite sizes were systematically re-investigated. Syntheses in the presence of triethanolamine with or without added bis(2-hydroxyethyl)dimethylammonium chloride yielded large crystals (10–100 μm) of faujasite-type zeolites. However, only products with low n Si/ n Al-ratios below 1.8 were obtained, and zeolite P was an inevitable side product or even the main product. Furthermore, the outcome of these syntheses was poorly reproducible. Following another known literature procedure, phase-pure zeolite Y could be obtained with the cyclic polyether 15-crown-5 as a structure-directing agent. The influence of ageing, homogenization and seeding of the synthesis gel, the crystallization time and temperature, different Si- and Al-sources and the addition of NaF as a mineralizer or of co-templates such as triethanolamine, ethylene glycol or 1,3,5-trioxane on the resulting product was investigated. A carefully optimized procedure led to large crystals of highly phase-pure zeolite Y with well defined octahedral morphology and a narrow crystal size distribution in the range of 4–5 μm. Such crystals can be reproducibly synthesized in high yields with an n Si/ n Al-ratio of 3.4–4.0. Neither crystallization seeds nor an ageing of the synthesis gel before hydrothermal crystallization are required.